Stats means business : statistics with Excel for business, hospitality and tourism / John Buglear - Buglear, John
Suitable for Business, Hospitality and Tourism students who take modules on Statistics or Quantitative research methods, this book enables readers to appreciate the importance of statistical analysis in business, hospitality and tourism. It includes content related to Hospitality and Tourism courses.